Analisis belanja daerah pada Kabupaten Induk dalam Provinsi Jambi - Bagas Pradyastio; Selamet Rahmadi; Yohanes Vyn Amzar (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2019)
This study aims to determine whether economic growth, population, and local original income affect regional spending in the Main District in Jambi Province. The data used in this study are secondary data for 5 years, namely from 2012 to 2016. The variables used are regional expenditure, economic growth, population, and locally-generated revenue(PAD) in Parent Regencies in Jambi Province. The analytical tool used in this study is a simple linear regression and multiple linear regression using panel data. The results of data processing obtained the following results. First, economic growth does not significantly influence regional spending. Second, the population has a significant influence on regional spending. Third, the PAD has a significant effect on regional expenditure. Fourth, when viewed together it can be concluded that only PAD has a positive and significant effect, while economic growth and population do not affect regional spending in Parent Regencies in Jambi Province. Keywords: Regional expenditure, Economic growth, Total population, locally-generated revenue (PAD)